Successful therapy using high-dose furmonertinib for non-small cell lung cancer with leptomeningeal metastasis: a case report and literature review - Chen, Ting; Chen, Jie; Liu, De-sheng; Shu, Yan-ling; Fu, Mao-yue; Gou, Hai-jun; Lei, Kai-jian; Jia, Yu-ming (Frontiers in Oncology, 2023)
Background Lung cancer is the second most common form of malignant tumor and has the highest mortality rate worldwide. Among its subtypes, lung adenocarcinoma is the most prevalent. Leptomeningeal metastasis (LM) is rare and is characterized by a dismal prognosis, with overall survival periods typically spanning 4 to 6 weeks without treatment. However, in specific cases, survival can be extended to 4 to 6 months with appropriate therapy. The recent approval of third-generation tyrosine kinase inhibitors (TKIs), such as osimertinib, aumolertinib, and furmonertinib, has introduced promising treatment options for individuals with non-small cell lung cancer (NSCLC) who develop LM after developing resistance to first- and second-generation TKIs. These third-generation TKIs exhibit an enhanced ability to penetrate the blood–brain barrier (BBB), opening up new avenues for managing this challenging condition. Case summary We report the case of a 48-year-old Chinese man diagnosed with advanced NSCLC harboring an epidermal growth factor receptor (EGFR) mutation. Following a pulmonary lobectomy and postoperative adjuvant therapy with gefitinib, the patient was diagnosed with LM, which was confirmed by his neurologic symptoms, cerebrospinal fluid cytologic analysis, and cranial enhancement magnetic resonance imaging. Subsequently, he received oral treatment in the form of 160 mg of furmonertinib daily. After 5 days of furmonertinib therapy, the patient recovered from lethargy, with an obvious improvement in cognitive function. Follow-up visits revealed a 6-month survival period following the LM diagnosis. Patients with NSCLC and LM typically present with severe symptoms, and the efficacy of systemic treatment, intrathecal chemotherapy, and radiotherapy remains unsatisfactory. We hope that this specific case provide valuable insights into the management of patients with EGFR mutation-associated NSCLC with LM. Conclusion Furmonertinib, a third-generation EGFR TKI with notable BBB penetration, shows promise in LM control and the rapid alleviation of intracranial symptoms. Further investigations into appropriate dosage and toxicity management are imperative.